(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe some adverse reactions after receiving the AstraZeneca COVID-19 vaccine at Hai Duong Medical University in 2022. Research Method: A descriptive cross-sectional study was conducted to describe some adverse reactions in subjects who received the AstraZeneca COVID-19 vaccine. The research team distributed questionnaires to 261 officials, employees, and students of Hai Duong Medical University who had received the AstraZeneca COVID-19 vaccine and completed all four doses. Research Results: The study was conducted on 261 subjects. The most common injection site reaction was pain at the first dose (51.7%), followed by burning (27.2%) and itching (10.3%). The most common systemic reactions were fever and fatigue, with fever occurring in 45.2% of subjects at the first dose. Headache was the most common neurological reaction, appearing in 77.0% of subjects at the first dose and remaining above 70% at subsequent doses. Common musculoskeletal reactions included body aches (45.2% at the first dose) and joint pain (46.7% at the fourth dose), while respiratory reactions were primarily sore throat, accounting for approximately 49.4–52.1% across all injections. In conclusion: Some of the most common post-vaccination reactions to the AstraZeneca COVID-19 vaccine are pain, warmth, redness, itching, and swelling at the injection site. Other reactions include fatigue, headache, dizziness, muscle pain, joint pain, body aches, sore throat, runny nose, cough, and fever. In addition, some less common reactions include nausea and swelling at the injection site.